The main stages of ore formation of the Svetloe epithermal gold deposit (Khabarovsk Region) based on the study of the mineral composition of metasomatic rocks and ores - Levochskaya D. V.; Yakich T. Yu.; Lesnyak D. V.; Rudmin M. A.; Ruban A. S.; Erofeev A. E.; Mazurov A. K. (Руды и металлы, 2023)
The study of the spatiotemporal relationships of metasomatites and ores of various zones of the epithermal Au-Ag deposit Svetloe (Khabarovsk Region) using a traditional mineralogical and petrographic approach made it possible to establish several stages of ore formation confined to two paleovolcanic structures of the central type. The early stage corresponds to the moderately acidic (IS) type of mineralization, the second stage of ore formation corresponds to the acidic sulfate (HS) type. Gold mineralization associated with the early stage of ore formation is represented by two main types: Au-Ag-Te and Au-Ag. The late stage of mineralization is characterized by the predominance of redeposited high-grade gold, as well as the presence of other native elements: tellurium, selenium, sulfur, and bismuth.